WHAT PRE-PARTICIPATION HEALTH COMPLAINTS AND ATHLETE CHARACTERISTICS PREDICT INJURY AND ILLNESS AT MAJOR ATHLETICS CHAMPIONSHIPS? COHORT STUDY AT THE BEIJING 2015 IAAF WORLD CHAMPIONSHIPS. Issue 4 (1st February 2017) - Timpka, Toomas; Jacobsson, Jenny; Bargoria, Victor; Periard, Julien; Racinais, Sébastien; Ronsen, Ola; Halje, Karin; Andersson, Christer; Dahlström, Örjan; Spreco, Armin; Edouard, Pascal; Alonso, Juan Manuel
Abstract : Background: During the month before world championships in individual sports, about one-third of athletes are disturbed by injury complaints. Athletics athletes reporting a pre-championship gradual-onset injury complaint are known to be at increased risk to sustain an injury at the upcoming competitions. Predictors for in-championship illness and the predictive value of anxiety associated with pre-participation injury and illness complaints have not been investigated. Objective: To determine pre-participation predictors of injury and illness at a major Athletics championship. Design: Prospective cohort study. Setting: The 2015 IAAF World Championships in Athletics. Participants: 307 (32.1%) of 957 athletes in 50 national teams that accepted to participate. Assessment of Risk Factors: Sex, age, home continent, event category and pre-participation health complaints with qualifiers (injury or illness complaint, onset type (injury complaints only), reduction in participation, severity estimated by duration of time loss, associated anxiety, expected performance impact, etc.). Main Outcome Measurements: In-championship injury and in-championship illness. Results: 116 athletes (38.3%) of the participating athletes reported an injury complaint during the month before the championships, while 40 athletes (13%) reported an illness complaint. Twenty athletes (6.5%) sustained an injury or illness during the championships. Endurance athletes were almost tenfold more likely to sustain an in-championship illness than speed/power athletes (OR, 9.88; 95% CI, 1.20–81.31; P =0.033). Participants reporting a pre-participation gradual-onset injury complaint were three times more likely (OR, 3.09; 95% CI, 1.08–8.79; P =0.035) and those reporting an illness complaint causing anxiety were fivefold more likely (OR, 5.56; 95% CI, 1.34–23.15; P =0.018) to sustain an in-championship injury. Conclusions: Endurance athletes require particular clinical attention at major Athletics championships. Pre-participation complaints causing anxiety are interesting predictors for in-championship health problems. Diagnostic criteria for different types of exertion-related illness and the clinical and educational services provided to athletes preparing for championships in individual sports warrant further study.